Trojan-Like Internalization of Anatase Titanium Dioxide Nanoparticles by Human Osteoblast Cells - Ribeiro, A. R. [UNESP]; Gemini-Piperni, S. [UNESP]; Travassos, R.; Lemgruber, L.; Silva, R. C.; Rossi, A. L.; Farina, M.; Anselme, K.; Shokuhfar, T. [UNESP]; Shahbazian-Yassar, R. [UNESP]; Borojevic, R. [UNESP]; Rocha, L. A. [UNESP]; et al. (Nature Publishing Group, 2016)
Dentistry and orthopedics are undergoing a revolution in order to provide more reliable, comfortable and long-lasting implants to patients. Titanium (Ti) and titanium alloys have been used in dental implants and total hip arthroplasty due to their excellent biocompatibility. However, Ti-based implants in human body suffer surface degradation (corrosion and wear) resulting in the release of metallic ions and solid wear debris (mainly titanium dioxide) leading to peri-implant inflammatory reactions. Unfortunately, our current understanding of the biological interactions with titanium dioxide nanoparticles is still very limited. Taking this into consideration, this study focuses on the internalization of titanium dioxide nanoparticles on primary bone cells, exploring the events occurring at the nano-bio interface. For the first time, we report the selective binding of calcium (Ca), phosphorous (P) and proteins from cell culture medium to anatase nanoparticles that are extremely important for nanoparticle internalization and bone cells survival. In the intricate biological environment, anatase nanoparticles form bio-complexes (mixture of proteins and ions) which act as a kind of 'Trojan-horse' internalization by cells. Furthermore, anatase nanoparticles-induced modifications on cell behavior (viability and internalization) could be understand in detail. The results presented in this report can inspire new strategies for the use of titanium dioxide nanoparticles in several regeneration therapies.